(3GdCReI GdZPGFjI GdYGdejI (B:s (3JHYGJ GdYhdeI GdGbJUGOjI h GdJcGed GdOhdj (B/s - (3GdeNGOej, YHO GdbGOQ QRjbs ((3GdbGgQI(B: s (3OGQ GdaLQ(B, s, 2009)
1)(3GdhVY GdZPGFj aj GdYGde (B: (3JMbjb GdGcJaGA GdPGJj , GdCReI GdZPGFjI GdYGdejI (B2) (3CReI GdZPGA aj GdYGde GdKGdK (B: (3CReI GdZPGA h NWQ GdeLGYI , GdBKGQ GdSdHjI ddeSGYOGJ GdZPGFjI , GdHfc GdYGdej h GdCQbGe GdeNjaI (B3) (3GdehGQO GdWHjYjI h GdHTQjI aj GdhXf GdYQHj (B: (3GdeYWjGJ GdLZQGajI ddhWf GdYQHj , GdehGQO GdRQGYjI , GdehGQO GdeGFjI , GdjO GdYGedI aj GdeLGd GdRQGYj , GdGfJGL GdfHGJj h GdMjhGfj h GdSecj (B4) (3CReI GdZPGA aj GdhWf GdYQHj (B: (3GdGSJgdGc GdYQHj ef GdZPGA , GdGfJGL GdYQHj ef GdZPGA h CHYGO GdGReI GdZPGFjI (B5) (3cja jecf ehGLgI GdGReI GdZPGFjI (B: (3CReI GdYLR GdZPGFj h SHd VeGf GdGef GdZPGFjs
(3edGMb U(B. 149 (3eQGLY U (B.255 (3; cTGa GdJhGQjN U(B.227s
Keywords: (3GdCReGJ GdGbJUGOjIs; (3GdJcGed GdOhdjs; (3GdYhdeI GdEbJUGOjIs